Динаміка коливань очисника головок коренеплідних культур від залишків гички на корені - Булгаков, Володимир Михайлович; Адамчук, Валерій Васильович; Надикто, Володимир Трохимович; Будзанівський, М. І.; Bulgakov, Volodymyr; Adamchuk, Valery; Nadykto, Volodymyr; Budzanivskyi, M. (Київ : 2023, 2023)
UA: Дослідити вплив конструктивних параметрів очисника головок коренеплідних культур від залишків гички на корені на основі аналізу математичної моделі, яка описує його плоскопаралельний рух у поздовжньо-вертикальній площині за умови дії зовнішнього збурення у вигляді коливань ординат поздовжнього профілю поля. Методи. Теоретичні розрахунки математичної моделі функціонування задньоначіпного очисника головок коренеплідних культур проводили на комп’ютері із застосуванням програмного середовища PTC Mathcad 15.0 і сформованих для цього вихідних числових даних. Результати. Із застосуванням математичного моделювання визначено вплив коливань нерівностей поздовжнього профілю поля на кутові коливання очисника головок коренеплідних культур у поздовжньо-вертикальній площині проєкцій за різних значень коефіцієнтів жорсткості та демпфірування його опорно-копіювальних коліс, а також вплив поздовжньої координати розміщення цих коліс на рамі очисника. Висновки. Коефіцієнт жорсткості шин (7.50R16) опорно-копіювальних коліс очисника коренеплідних культур має перебувати на рівні 315 кН ⋅ м–1, що забезпечується за рахунок установлення тиску повітря у цих шинах 135 кПа. Значення коефіцієнта демпфірування шин опорно-копіювальних коліс очисника в діапазоні 350 – 1350 Н ⋅ с ⋅ м–1 не впливає на амплітудні і фазові частотні характеристики його кутових коливань за умови, коли коливання ординат поздовжнього профілю поля діють у діапазоні частот 0 – 24 с–1, і мало залежить від зміни значення поздовжньої координати розміщення його опорно-копіювальних коліс. З урахуванням характеру функціонування очисника головок коренеплідних культур під впливом коливань ординат поздовжнього профілю поля у визначальному діапазоні частот 0 – 24 с–1 місце фактичного розміщення його опорно-копіювальних коліс має визначатися з урахуванням особливостей конструкції машини. EN: The study of the influence of the design parameters of the cleaner of the heads of root crops from the remains of the chaff on the basis of the analysis of a mathematical model that describes its plane-parallel movement in the longitudinal-vertical plane under the influence of external disturbance in the form of fluctuations of the ordinates of the longitudinal profile of the field. Methods. Theoretical calculations of the mathematical model of the operation of the rear-mounted cleaner of the heads of root crops were performed on a computer using the PTC Mathcad 15 software environment and the initial numerical data generated for this purpose. The optimal value of the parameter was considered, for which the actual amplitude-frequency characteristics of the root crop cleaner were as close as possible to zero, and the phase-frequency characteristics were as large as possible. Results. By means of mathematical modeling, the influence of the fluctuations of the longitudinal profile of the field on the angular oscillations of the cleaner of root crop heads in the longitudinal-vertical plane of projections for different values of the stiffness and damping coefficients of its support-copying wheels, as well as the longitudinal coordinates of their placement on the cleaner frame, was determined. Conclusions. The value of the stiffness coefficient of the tires (7.50R16) of the supporting and copying wheels of the root crop cleaner should be at the level of 315 kN ⋅ m–1, which is ensured by setting the air pressure in the indicated tires at the level of 135 kPa. A change in the value of the damping coefficient of the tires of the supportcopying wheels of the root crop head cleaner in the range of 350...1350 N ⋅ s ⋅ m–1 practically does not affect the amplitude and phase frequency characteristics of its angular oscillations under the condition of the effect of oscillations of the ordinates of the longitudinal profile of the field in the determining frequency range 0...24 s–1 depends little on the change in the value of the longitudinal coordinate of the location of its supporting and copying wheels. Taking into account the nature of the operation of the head cleaner of root crops under the influence of fluctuations of the ordinates of the longitudinal profile of the field in the defining frequency range of 0...24 s–1, the place of actual placement of its supporting and copying wheels should be determined taking into account the features of the machine design.
Fluctuations dynamics of the root crops cleaner heads from the remnants of tops on the root
Keywords: корнеплідні культури; гичка; збирання; залишки; очищення; кутові коливання; жорсткість; демпфірування; диференціальне рівняння руху; розв’язок на ПК; root crops; ghee; harvesting; residues; cleaning; angular oscillations; stiffness; damping; differential equation of motion; solution on PC